KIYAI AND JAWARA TOWARD GENDER PHILOSOPHY IN SERANG DISTRICT, PANDEGLANG, LEBAK DAN CILEGON CITY - Faridatul Fauziah; Muchammad Fauzan Muchlis; Giantoro Pamungkas (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Banten is known as religious province. Islam has been became the Banten culture identity. Banten is known as the province that is very faith to Islam, so that the Kiyai is placed as most important person in society. The roles and position of Kiyai wich is strategic, it makes Kiyai don’t only live in boarding that they lead, but also they live in a large society. Although the society are known opened, but the structure of society in social life is very patriarchy. The social life is still traditional. It same with the other society, the society is still paternalistic and patriarchy. So that, to know the level of society aware toward the gender comprehension, this research is done. The approach which is used by using the kinds of knowledges, such as ethnography, history and theologic. While the collecting and analyze technique of data use the techniques Observation and implicated observation, Interview, Questionnaires. In accordance with the objectives of this study, to explore the position and status in the community Kiyai and champion Bante, and their views on gender equality, this study will use qualitative approach. The conclusion, of this result, The role of Kiyai is as religion elite social in Banten community (kokolot), a religion teacher. Beside that, he is a heir of religion tradition. Because of that, Kiyai gives the intend toward the social life. While the social role of Jawara is more disposed toward process of physic and supranatural powers. The tradition role of Jawara is to be a Jaro or village chief, the supranatural teacher and security unit. The role is be ever when the society in confusion and disturbance in long time. Whereas the gender sensitivitas in religion concept about the household tasks sharing is still far from the equal gender. The philosophy of Kiyai about the ne essity of women roles in social activity limit is still not satisfied, so that the women in Banten to express theirselves. It has correlation towards household tasks divided positively with women activities to join social activities. So that the women meet obstacle culturally to express theirselves, because the both of figures (KIyai and Jawara) who have influence toward Banten community which have aware about the equal of gender.